THE EFFECTS OF STUDENT’S PERCEPTION ON ROLE PLAY TECHNIQUE AND STUDENTS’ LEARNING MOTIVATION ON SPEAKING SKILLS - Sufi Alawiah; Suwarsito Suwarsito (Wanastra: Jurnal Bahasa dan Sastra, 2018)
Abstract : This research is a kind of survey and aims to find out and analyze empirically the effects of student’s perception on role play and students’ learning motivation on speaking skills. The observed population of this research is IX grade students of  State Junior High School, North Jakarta, which total of 195 students on six classes (9-1, 9-2, 9-3, 9-4, 9-5, 9-6). While the samples are 66 students which are divided evenly 11 students per class. The collection of the data is done by questionnaire and objective test for independent and dependent variables. The gained data was then analyzed by using correlation technique and double linier regression. The result of this research are: 1)There is a significant effect of student’s perception on role play method and learning motivation jointly on student’s speaking skill, based on the ANOVA table, the sig. value revealed is 0.000 which is lower than 0.05. Since sig. value < 0.05; 2) There is a significant effect of student’s perception on role play method on students’ speaking skill, since t value > t (2.999 > 1.998); 3) There is a significant effect of learning motivation on students’ speaking skill, since t value > t (5.119> 1.998). The findings of the research shows that all indicators for student’s perception on role play, motivation and speaking skill variables are valid and reliable. The mean scores show that the students felt Agree to the Roleplay, and felt Strongly Agree both to the Motivation and Speaking Skill, which can be concluded that the students are showing positive respond to Role Play and Strong Positive responds on Motivation and Speaking Skill.The hypothesis testing revealed that Role play method and motivation has significant partial and simultaneous effect on students’ speaking skill. Role play facilitate students to communicate and understand what they are communicating and what the other are saying. The motivation of the students encourage the student to intensively engaged in English language by communicating-speaking and listening as well to provide feedback based on the partners’ oral communication, thus enhance speaking skill.